2017
DOI: 10.7554/elife.29062
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reconstitution of yeast Mpp6-nuclear exosome complexes reveals that Mpp6 stimulates RNA decay and recruits the Mtr4 helicase

Abstract: Nuclear RNA exosomes catalyze a range of RNA processing and decay activities that are coordinated in part by cofactors, including Mpp6, Rrp47, and the Mtr4 RNA helicase. Mpp6 interacts with the nine-subunit exosome core, while Rrp47 stabilizes the exoribonuclease Rrp6 and recruits Mtr4, but it is less clear if these cofactors work together. Using biochemistry with Saccharomyces cerevisiae proteins, we show that Rrp47 and Mpp6 stimulate exosome-mediated RNA decay, albeit with unique dependencies on elements wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 63 publications
6
74
0
1
Order By: Relevance
“…In particular, the nuclear Rrp47 cofactor interacts with Rrp6 via intertwined helices that form a composite surface, binding to Mtr4 of the TRAMP complex and other complexes and recruiting Mtr4 to the RNA exosome (Schuch et al 2014). Furthermore, the nuclear Mpp6 cofactor interacts with the Rrp40 cap subunit and can also recruit Mtr4 to the RNA exosome (Falk et al 2017;Wasmuth et al 2017). The cytoplasmic Ski7 cofactor interacts with the Csl4 cap subunit and two ring subunits, Mtr3 and Rrp43 (Kowalinski et al 2016).…”
Section: Comparisons and Potential Mechanisms Of Exosomelinked Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the nuclear Rrp47 cofactor interacts with Rrp6 via intertwined helices that form a composite surface, binding to Mtr4 of the TRAMP complex and other complexes and recruiting Mtr4 to the RNA exosome (Schuch et al 2014). Furthermore, the nuclear Mpp6 cofactor interacts with the Rrp40 cap subunit and can also recruit Mtr4 to the RNA exosome (Falk et al 2017;Wasmuth et al 2017). The cytoplasmic Ski7 cofactor interacts with the Csl4 cap subunit and two ring subunits, Mtr3 and Rrp43 (Kowalinski et al 2016).…”
Section: Comparisons and Potential Mechanisms Of Exosomelinked Diseasementioning
confidence: 99%
“…EXOSC2/3/8 variants could therefore potentially alter interactions with EXOSC10/Rrp6, C1D/Rrp47, hMPP6/Mpp6, or HBS1L3/ Ski7 to cause tissue-specific disease, if interactions of the human exosome cofactor orthologs with the human RNA exosome are conserved. As EXOSC10/Rrp6, C1D/Rrp47, and hMPP6/Mpp6 all facilitate recruitment of hMTR4/Mtr4 (Schilders et al 2007;Lubas et al 2011;Falk et al 2017;Wasmuth et al 2017) and Ski7 interacts with the Ski complex (Araki et al 2001;Wang et al 2005;Kowalinski et al 2016), EXOSC2/3/8 variants could also differentially impair interactions with the NEXT, TRAMP, and Ski complexes to cause disease. Certainly, the EXOSC2/3/8 subunits could also specifically interact with different, as-yet unidentified, tissue-specific exosome cofactors and therefore the EXOSC2/3/8 variants would only affect tissues that harbor a subunit-specific exosome cofactor.…”
Section: Comparisons and Potential Mechanisms Of Exosomelinked Diseasementioning
confidence: 99%
“…First, amino acid substitutions could directly alter interactions with specific target RNAs. In budding yeast, the three cap subunits of the RNA exosome make direct contact with RNA [8,33], and the integrity of the S1/KH cap subunit ring is critical for the path of RNA to Rrp6, the nuclear catalytic subunit of the exosome [33].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cofactors associate with the RNA exosome to confer specificity for target RNAs and/or facilitate the unwinding of structured RNAs [34]. Indeed, structural studies show that the nuclear RNA exosome cofactor Mpp6 interacts with the Rrp40 cap subunit [33,36], and that an amino acid change in Rrp40 that models a change in PCH1b decreases the interaction of Mpp6 with the RNA exosome [36]. The idea that interactions with specific cofactors could be perturbed by the amino acid changes that occur in disease is attractive because altered interactions with cofactors in different tissues or cell types could explain the phenotypic variation Morton et al 14 observed for mutations within the same EXOSC gene or the different EXOSC subunit genes that are linked to distinct diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation